1998
DOI: 10.2754/avb199867020103
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cadmium Concentrations in Tissues of Different Categories of Cattle

Abstract: Concentrations of cadmium in selected tissues collected from various categories of Black Pied cattle were compared. All the animals, including 7 cows aged 3 to II years. four heifers aged 26 to 28 months. 14 bulls aged 24 to 26 months. and 7 calves aged 4 to 6 months. were kept at a single farm. Samples of hepatic. renal. myocardial. and diaphragmatic tissues were collected after slaughter. The samples were mineralized using the microwave digestion technique and cadmium was determined by the ETA·AAS method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
3
5
0
Order By: Relevance
“…The increase in Cd concentration in cow kidney is most probably connected with the age of animals as documented e.g. by Pechová et al (1998) who confirmed the highly significant relation between the age of cows and Cd content in kidney. Unfortunately, data describing the mean age of cows slaughtered in the Czech Republic are not fully available for the entire examined period, but it is apparent that it was growing with time up to about 72 months.…”
Section: Discussionsupporting
confidence: 52%
“…The increase in Cd concentration in cow kidney is most probably connected with the age of animals as documented e.g. by Pechová et al (1998) who confirmed the highly significant relation between the age of cows and Cd content in kidney. Unfortunately, data describing the mean age of cows slaughtered in the Czech Republic are not fully available for the entire examined period, but it is apparent that it was growing with time up to about 72 months.…”
Section: Discussionsupporting
confidence: 52%
“…The reported average liver Cd concentrations varies from 1.5 to 5.8 times those found in the present study. [39][40][41]50,[52][53][54][56][57][58][59] The Cd levels reported in the literature for muscle are low but the means are 2-280 times higher than in our study. [39][40][41]50,[52][53][54][56][57][58][59] For cows from noncontaminated areas and of similar age as in the present study the kidney Cd levels are similar.…”
Section: Discussionmentioning
confidence: 47%
“…The retention of Cd in kidney cortex is well known from humans 34 and several animal species, e.g., horses, 35,36 rodents, 37 pigs 28 and cattle. [38][39][40][41] The increase in growing finishing pig kidneys is y15 mg kg 21 month 21 as shown by Linde ´n et al 28 However, these animals are only about 6 months old at slaughter and mono-gastric, which may explain the more rapid accumulation in pig kidneys than in cow kidneys. Koh et al 39 showed that the maximum permissible concentration of Cd in kidney (2500 mg kg 21 ) in Australia was exceeded more frequently in older cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of cadmium concentrations, as well as those of other "heavy metals", in the tissues of farm animals was dealt with, e.g., by Doganoc (1996), Pechova et al (1998). The authors demonstrated a higher cadmium cumulation in the kidney and liver dependent on the age of the cattle.…”
Section: Discussionmentioning
confidence: 99%